Kinetics and Mechanism of the Oxidation of Adonitol by Hexacyanoferrate(III) Ion in Aqueous Alkaline Medium - Quadri, N.F.; Patel, N.T. (Asian Journal of Chemistry, 2010)
The rate of oxidation of adonitol by hexacyanoferrate(III) ion in aqueous alkaline medium is directly proportional to the organic substrate and hydroxide ion concentration. The rate of hexacyanoferrate(lll) ion is flfst order at considered concentrations. A probable mechanism has been suggested.